Challenges And Importance Of Knowledge Sharing : A Case Study In Cyberjaya Community - Zargham, Alireza (2006)
This research limits the field of investigation to the challenges and barriers of knowledge sharing within the Malaysian organizations. In this study the focus is on two specific areas. Fisrtly, to what extent managers are familiar with knowledge management issues and secondly, which are the potential individual and organizational barriers to knowledge sharing.